Plasmodium falciparum chloroquine resistance transporter (PfCRT) isoforms PH1 and PH2 perturb vacuolar physiology. (December 2016) - Callaghan, Paul; Siriwardana, Amila; Hassett, Matthew; Roepe, Paul
Abstract Background Recent work has perfected yeast-based methods for measuring drug transport by thePlasmodium falciparum chloroquine (CQ) resistance transporter (PfCRT). Methods The approach relies on inducible heterologous expression of PfCRT inSaccharomyces cerevisiae yeast. In these experiments selecting drug concentrations are not toxic to the yeast, nor is expression of PfCRT alone toxic. Only when PfCRT is expressed in the presence of CQ is the growth of yeast impaired, due to inward transport of chloroquine (CQ) via the transporter. Results During analysis of all 53 known naturally occurring PfCRT isoforms, two isoforms (PH1 and PH2 PfCRT) were found to be intrinsically toxic to yeast, even in the absence of CQ. Additional analysis of six very recently identified PfCRT isoforms from Malaysia also showed some toxicity. In this paper the nature of this yeast toxicity is examined. Data also show that PH1 and PH2 isoforms of PfCRT transport CQ with an efficiency intermediate to that catalyzed by previously studied CQR conferring isoforms. Mutation of PfCRT at position 160 is found to perturb vacuolar physiology, suggesting a fitness cost to position 160 amino acid substitutions. Conclusion These data further define the wide range of activities that exist for PfCRT isoforms found inP. falciparum isolates from around the globe. Graphical abstract V5 Western blot quantifying relative PfCRT expression in total (CM) vs vacuolar (VAC) yeast membranes for unmodified HB3 PfCRT vs HB3 and PH1 PMA–PfCRT chimeras.